Limosilactobacillus fermentum Strain 3872: Antibacterial and Immunoregulatory Properties and Synergy with Prebiotics against Socially Significant Antibiotic-Resistant Infections of Animals and Humans - Vyacheslav M. Abramov; Igor V. Kosarev; Andrey V. Machulin; Tatiana V. Priputnevich; Irina O. Chikileva; Evgenia I. Deryusheva; Tatiana N. Abashina; Almira D. Donetskova; Alexander N. Panin; Vyacheslav G. Melnikov; Nataliya E. Suzina; Ilia N. Nikonov; et al. (MDPI AG, 2022)
Limosilactobacillus fermentum strain 3872 (LF3872) was originally isolated from the breast milk of a healthy woman during lactation and the breastfeeding of a child. The high-quality genome sequencing of LF3872 was performed, and a gene encoding a unique bacteriocin was discovered. It was established that the bacteriocin produced by LF3872 (BLF3872) belongs to the family of cell-wall-degrading proteins that cause cell lysis. The antibacterial properties of LF3872 were studied using test cultures of antibiotic-resistant Gram-positive and Gram-negative pathogens. Gram-positive pathogens (Staphylococcus aureus strain 8325-4 and S. aureus strain IIE CI-SA 1246) were highly sensitive to the bacteriolytic action of LF3872. Gram-negative pathogens (Escherichia coli, Salmonella strains, and Campylobacter jejuni strains) were more resistant to the bacteriolytic action of LF3872 compared to Gram-positive pathogens. LF3872 is a strong co-aggregator of Gram-negative pathogens. The cell-free culture supernatant of LF3872 (CSLF3872) induced cell damage in the Gram-positive and Gram-negative test cultures and ATP leakage. In the in vitro experiments, it was found that LF3872 and Actigen prebiotic (Alltech Inc., Nicholasville, KY, USA) exhibited synergistic anti-adhesive activity against Gram-negative pathogens. LF3872 has immunoregulatory properties: it inhibited the lipopolysaccharide-induced production of proinflammatory cytokines IL-8, IL-1β, and TNF-α in a monolayer of Caco-2 cells; inhibited the production of IL-12 and stimulated the production of IL-10 in immature human dendritic cells; and stimulated the production of TGF-β, IFN-γ, and IgA in the immunocompetent cells of intestinal Peyer's patches (PPs) in mice. These results indicate the possibility of creating a synbiotic based on LF3872 and a prebiotic derived from Saccharomyces cerevisiae cell wall components. Such innovative drugs and biologically active additives are necessary for the implementation of a strategy to reduce the spread of antibiotic-resistant strains of socially significant animal and human infections.